The Cost of Islamic Boarding School Electricity Bills is Lowered by Installing Solar Cells on Grid Limiters - Parlin Siagian; M. Erpandi Dalimunthe; Bahtiar Siregar; M. Fadlan; Ridho Anggu Frasasti (PT FORMOSA CENDEKIA GLOBAL, 2022)
The world's supply of fossil energy is currently decreasing, and in time it will be scarce, while the human need for energy continues to increase. Solar cells that utilize solar energy are a source of renewable electrical energy (EBT). The burden of electricity bills at the Fajrul Iman Patumbak Modern Islamic Boarding School, Deli Serdang Regency is quite a burden on Islamic boarding school expenses. To reduce the burden of spending on electricity bills at Islamic boarding schools, solar cells and control equipment are installed so that they can generate electricity. After this service is carried out, the cost of spending on Islamic boarding schools has decreased. From this decrease, other Islamic boarding schools who know about this program are excited to utilize solar cells as a source of electric power. In the end, this program became a pilot for Islamic boarding schools that used EBT. All of these hopes can be seen in the dedication video that has been broadcast on the YouTube channel.